Green Marketing Mentoring for MSMEs in Rowokangkung District - Robustin, Tri Palupi; Irdiana, Sukma; Putri, Nur Latifa Isnaini (IMPOWERMENT SOCIETY, 2025)
Green Marketing is a marketing activity that uses environmental issues as a strategy to market products. The purpose of this green marketing training mentoring activity is to contribute to the community in Sidorejo Village who have businesses to be able to implement green marketing strategies in the form of green product features, green product prices, green product promotions in their businesses, so that they can improve their business image. This community service has provided several results, including the first activity is providing knowledge to the Sidorejo Village community about green marketing, so that they understand the importance of environmentally friendly marketing activities and the extraordinary benefits for health and environmental sustainability. This activity also provided good feedback because during the activity, many people were enthusiastic to ask questions related to the material presented. In addition, as many as 50 participants showed an increased understanding of green marketing strategies based on the results of the evaluation of the activity.